Analysis of Transcriptionally Active Bacteria Throughout the Gastrointestinal Tract of Healthy Individuals - Vasapolli, Riccardo; Schütte, Kerstin; Schulz, Christian; Vital, Marius; Schomburg, Dirk; Pieper, Dietmar H.; Vilchez-Vargas, Ramiro; Malfertheiner, Peter (Gastroenterology (New York, N.Y. 1943), 2019)
The microbiome varies along the human gastrointestinal (GI) tract with exposure to luminal and mucosal factors. We analyzed active bacterial communities at 8 locations along the GI tract using high-throughput sequencing techniques. We collected saliva, mucosal, and fecal samples from healthy adults (10 men and 11 women; mean age, 59 ± 12.3 years) who underwent upper and lower GI tract endoscopy in Germany from December 2015 through September 2016. Biopsies were taken from stomach, antrum, corpus, duodenum, terminal ileum, ascending colon, and descending colon. RNA was extracted from all samples and reverse transcribed into complementary DNA; V1–V2 regions of 16S ribosomal RNA genes were amplified and sequenced on an Illumina MiSeq platform. Abundances of the taxa in all taxonomic ranks in each sample type were used to construct sample-similarity matrices with the Bray-Curtis algorithm. Significant differences between a priori–defined groups were evaluated using analysis of similarity. After taxonomic annotation, 4045 phylotypes, belonging to 169 genera and 14 different phyla, were identified. Each subject had a different bacterial community. We identified distinct microbial consortia in saliva, upper GI tract, lower GI tract, and fecal samples. The predominant genera in the upper GI tract (Gemella, Veillonella, Neisseria, Fusobacterium, Streptococcus, Prevotella, Pseudomonas, and Actinomyces) were almost absent from the lower GI tract, where the microbial communities mainly comprised Faecalibacterium, Ruminococcus, and Bacteroides. The bacterial communities in the upper GI tract were characterized by greater richness and heterogeneity (measured by the Shannon index) than those in the lower GI tract. We detected Helicobacter pylori in only the upper GI tract. In an analysis of saliva, mucosal, and fecal samples from 21 healthy adults, we found each individual, and each GI region, to have a different bacterial community. The fecal microbiome is not representative of the mucosal microbiome. We propose a systematic method to analyze the bacterial communities of the GI tract.